The Language of Climate Change Policy - Raphael Calel (Opticon1826, 2010)
Although the Copenhagen Accord failed to establish a Post-Kyoto infrastructure for international efforts to reduce greenhouse gas emissions, countries around the world are moving ahead with domestic pledges and policies to cut carbon. Sweden, Denmark, Finland, and Ireland already have domestic carbon taxes; Britain has just introduced a major energy efficiency scheme for buildings and announced plans to introduce an airplane tax; the EU Emissions Trading Scheme is being extended to include the aviation sector; Japan is moving ahead with plans to introduce a domestic cap-and-trade programme; several cap-and-trade bills have been circulating on the floor of the US Congress, and former Australian prime minister Kevin Rudd was recently ousted after reneging on promises of a comprehensive cap-and-trade scheme. The success of all these efforts depends crucially on compliance. If emitters do not comply with new regulations, it hardly matters what environmental policies are pursued. When choosing the instruments of environmental policy, therefore, it is essential to consider what level of compliance they will garner. The literature that examines this question usually compares the costs of compliance or monitoring across different environmental policy instruments, it being understood that lower costs lead to greater compliance. This note explores a different route to increasing compliance. A policy instrument determines what language the regulator, the emitter, and the public use to communicate about environmental and economic priorities. The language of environmental policy also determines the complexity of the messages being communicated. Different policy instruments may then invoke different attitudes toward non-compliance. One should not discount the potential these attitudes have in influencing efforts to comply with new environmental regulations. This exploratory note compares the 'languages' of three major policy instruments: direct regulation, carbon tax, and cap-and-trade.
Keywords: government regulation; global warming; climate change